Unusual enantioselective cytoplasm-to-nucleus translocation and photosensitization of the chiral Ru(II) cationic complex via simple ion-pairing with lipophilic weak acid counter-anions. Issue 7 (20th March 2023) - Chao, Xi-Juan; Huang, Chun-Hua; Tang, Miao; Yan, Zhu-Ying; Huang, Rong; Li, Yan; Zhu, Ben-Zhan
Abstract: Targeted and enantioselective delivery of chiral diagnostic-probes and therapeutics into specific compartments inside cells is of utmost importance in the improvement of disease detection and treatment. The classical DNA 'light-switch' ruthenium(II)-polypyridyl complex, [Ru(DIP)2 (dppz)]Cl2 (DIP = 4, 7-diphenyl-1, 10-phenanthroline, dppz = dipyridophenazine) has been shown to be accumulated only in the cytoplasm and membrane, but excluded from its intended nuclear DNA target. In this study, the cationic [Ru(DIP)2 (dppz)] 2+ is found to be redirected into live-cell nucleus in the presence of lipophilic 3, 5-dichlorophenolate or flufenamate counter-anions via ion-pairing mechanism, while maintaining its original DNA recognition characteristics. Interestingly and unexpectedly, further studies show that only the Δ-enantiomer is selectively translocated into nucleus while the Λ-enantiomer remains trapped in cytoplasm, which is found to be mainly due to their differential enantioselective binding affinities with cytoplasmic proteins and nuclear DNA. More importantly, only the nucleus-relocalized Δ-enantiomer can induce obvious DNA damage and cell apoptosis upon prolonged visible-light irradiation. Thus, the use of Δ-enantiomer can significantly reduce the dosage needed for maximal treatment effect. This represents the first report of enantioselective targeting and photosensitization of classical Ru(II) complex via simple ion-pairing with suitable weak acid counter-anions, which opens new opportunities for more effective enantioselective cancer treatment. Graphical Abstract: